Identifying patterns of change in fire protection of the tent fabric treated with an epoxy resin-based intumescent coating - Tsapko, Yuriy; Berdnyk, Oksana; Tsapko, Aleksii; Likhnyovskyi, Ruslan; Nehrii, Tetiana; Kasianova, Oksana; Feshchuk, Yurii; Lomaha, Vasyl; Bedratiuk, Olga; Bielikova, Kseniia (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process of forming a fire-retardant coating based on modified epoxy resin on the surface of tent fabric. The task addressed is to ensure fire protection of tent fabric when treated with a coating based on modified epoxy resin. This is important given the relevance of fire-resistant materials for modern construction. It has been proven that when treating tent fabric with epoxy resin, the free energy component of the fabric surface decreased by more than 2.3 times, while the polar component increased by 1.6 times, which indicates a change in the surface. At the same time, the tensile strength of tent fabric after treatment with epoxy resin increased by more than 4.1 times. The study has shown that a sample of tent fabric caught fire when exposed to a burner flame for 5 s and continued to burn for 16 s when the ignition source was removed. The treatment of tent fabric with epoxy resin with flame retardant led to the formation of charring on the sample with a length of more than 70 mm, and the height of the swelling in the flame zone was about 3 ÷ 5 mm. When testing tent fabric samples for the flame spread index, it was found that the sample treated with epoxy resin caught fire in 524 s, the flame spread throughout the sample for 14 s, the burning length of the sample was 300 mm, and the flammability index was 36.3. However, for samples treated with epoxy resin filled with a mixture of ammonium polyphosphate and aluminum hydroxide, the flammability indices decreased by more than 30 times. The optimal concentration of components in the coating containing 34 ÷ 35% (wt.) of ammonium polyphosphate and 9 ÷ 10% (wt.) of aluminum hydroxide has been determined. Thus, there are grounds for the possibility of designing fire-resistant coatings for construction